INCREASING ONLINE SALES BY UTILIZING FACEBOOK PRO AS A BUSINESS PROMOTION PLATFORM - Witi, Ferdinandus Lidang; Rawe, Aschari Senjahari (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology encourages businesses, particularly Micro, Small, and Medium Enterprises (MSMEs), to adopt digital-based marketing strategies to increase competitiveness and product sales. However, many MSMEs still have not optimally utilized social media as a means of business promotion. This community service activity aims to improve the knowledge and skills of MSMEs in utilizing Facebook Professional Mode (FB Pro) as an online business promotion platform. The implementation method includes training, direct practice, and mentoring in the use of FB Pro features, such as managing promotional content, utilizing insights or analytics, and strategies to increase audience engagement. This activity was carried out at the Ende BUMN House with the involvement of assisted MSMEs as training participants. The results of the activity showed an increase in participants' understanding of digital marketing concepts and their ability to manage FB Pro accounts for product promotion activities more effectively. In addition, participants were able to produce more structured and attractive promotional content and understand how to read analytical data as a basis for marketing decision-making. Thus, training on utilizing FB Pro as a business promotion platform can be a strategic solution to increase online sales and strengthen the digital marketing capacity of MSMEs in a sustainable manner.